Exclusivism and Radicalism in Schools: State Policy and Educational Politics Revisited - Abdallah, Abdallah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2016)
Religious Education is an important part of a nation’s political culture, and Indonesia is no exception. Since independence, Sukarno, Indonesia’s first president, insisted that the role of Islamic education was not only character-building but also nation-building. Islamic religious education is expected to have a stake in building the character of the nation and to participate in actualizing the promises of independence. The objective of Islamic education in Indonesia is not only to create a religious person, but also making a good citizen.The values ​​of piety assume that a person will be a good citizen: tolerant, democratic and respectful of others. However, practically, piety does not guarantee that a person is able to uphold such values ​​of citizenship. Today, religious radicalism which leads to violent behavior and labelling the other as unbeliever (takfīrīyah) is booming in the community. Ironically, the radical ideology infiltrates education sector. In Jombang, in March 2015, the Ansor Youth Movement (Gerakan Pemuda Ansor) associated with Nahdlatul Ulama found radical ideology on senior high school worksheets which called for killing people deemed idolatrous; the worksheet reads: “only Allah can and should be worshipped, and those who worship anything besides Allah have become idolatrous and should be killed.” As it turned out, this was not only in Jombang; the same materials can be found in Jakarta, Depok and Bandung.DOI: 10.15408/sdi.v23i3.4425